Company Size, Managerial Ownership, Sustainability Report on Financial Performance with Operational Efficiency as an Intervening - Alfariz, Rifa; Yuliastuty Asmara, Rina (Asian Journal of Social and Humanities, 2024)
The aim of this research is to examine the influence of company size, managerial ownership, and Sustainability Report on the financial performance of banking companies in Indonesia, with operational efficiency as an intervening variable. The population for this study comprises banking companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Data collection was conducted using purposive sampling, resulting in a sample of 13 companies and a total of 65 observations. The analysis technique employed is panel data regression. Microsoft Excel and E-views 13 were used for data processing. The research findings indicate that, partially, company size and managerial ownership have a positive effect on operational efficiency. However, the Sustainability Report does not significantly affect operational efficiency. Furthermore, company size and operational efficiency are empirically proven to have a positive impact on financial performance. Meanwhile, managerial ownership and Sustainability Report do not significantly influence financial performance. Company size and managerial ownership, mediated by operational efficiency, positively impact financial performance, while Sustainability Report which mediated by operational efficiency, does not significantly affect financial performance.